Sleep and executive functions in older adults: A systematic review - Francisco Wilson Nogueira Holanda Júnior; Katie Moraes de Almondes (Dementia & Neuropsychologia)
ABSTRACT Introduction: A recent increase in studies suggests a role of age-related sleep changes in executive functions (EF). However, this relationship remains unclear and mixed results have emerged. Objective: To investigate how age-related sleep changes may play an important role in the extent to which healthy older adults exhibit decline in EF. Methods: A systematic strategy was employed to identify the available literature on age-related sleep changes and EF. Results: Of the 465 studies identified, 26 were included. Results suggest that multiple sleep parameters differ in the way they benefit or impair EF. Parameters such as greater wake after sleep onset and lower sleep efficiency, in addition to circadian fragmentation of sleep, showed more consistent results and are potentially correlated with worsening in EF measures. However, other results seem inconclusive. Conclusion: These findings were discussed based on the prefrontal circuitry vulnerability model, in which sleep has been identified as a beneficial factor for prefrontal cortex functioning and hence for EF, which relies mostly on this brain area and its related networks.